(untitled) (Research, Society and Development, 2021)
Skin hyperchromias are common sequelae due to some disorder in the physiological process, including aging, hormonal changes, inflammation, allergies and excessive sun exposure. The tissue hyperpigmentation process occurs due to increased production of melanin by cells named melanocyte, tissue abnormality that affects many people and consequently their quality of life. Its objective is to describe through existing literature the benefits of kojic acid in the treatment of cutaneous hyperchromia. This study is an integrative literature review, using scientific articles and books that already exist on online platforms as a data source. Experimental and non-experimental researches were found that prove the effectiveness of the active kojic acid in its pure concentration or in combination with other lightening substances. Although there are few studies on the subject, it is concluded that the depigmenting active of kojic acid is a safe and efficient alternative in the treatment of spots, due to its natural and non-cytotoxic formulation.